Fire Resistance of Three-Phase Foam with Modified Hollow Glass Microspheres - Tang, Baohua (Asian Journal of Chemistry, 2014)
In this work, fluoroalkylsilane [F3C-(CF2)5-(CH2)2-Si(OC2H5)3, F-8261] was used as surface modifier for oleophobic hollow glass microspheres. Then three-phase foam was prepared with the modified oleophobic hollow microspheres. The results showed that the stability and antiburning properties of three-phase foam on oil were improved significantly. The optimum results were achieved with the addition of 12 % of fire fighting protein, 50 % of hollow microspheres and 0.5 % of F-8261.